Effect of ozonated water, mancozeb, and thiophanate-methyl on the phyllosphere microbial diversity of strawberry - Sun, Ping; Wu, Jiaqi; Lin, Xianrui; Wang, Yi; Zhu, Jianxi; Chen, Chenfei; Wang, Yanqiao; Jia, Huijuan; Shen, Jiansheng (Frontiers in Plant Science, 2022)
Phyllosphere microorganisms are closely linked to plant health. This study investigated the effect of ozonated water, mancozeb, and thiophanate-methyl on phyllosphere microorganisms in strawberry plants of the ‘Hongyan’ variety. Sequencing analysis of the phyllosphere bacterial and fungal communities was performed using 16S rRNA gene fragments and the ITS1 region high-throughput sequencing after spraying ozonated water, mancozeb, thiophanate-methyl, and clear water. Proteobacteria, Actinobacteria, and Firmicutes were the dominant bacterial phyla in strawberry. The relative abundance of Proteobacteria (82.71%) was higher in the ozonated water treatment group than in the other treatment groups, while the relative abundance of Actinobacteria (9.38%) was lower than in the other treatment groups. The strawberry phyllosphere fungal communities were mainly found in the phyla Basidiomycota and Ascomycota. The relative abundance of Basidiomycota was highest in the ozonated water treatment group (81.13%), followed by the mancozeb treatment group (76.01%), while the CK group only had an abundance of 43.38%. The relative abundance of Ascomycota was lowest in the ozonated water treatment group (17.98%), 23.12% in the mancozeb treatment group, 43.39% in the thiophanate-methyl treatment group, and 55.47% in the CK group. Pseudomonas, Halomonas, and Nesterenkonia were the dominant bacterial genera on strawberry surfaces, while Moesziomyces, Aspergillus, and Dirkmeia were the dominant fungal genera. Ozonated water was able to significantly increase the richness of bacteria and fungi and decrease fungal diversity. However, bacterial diversity was not significantly altered. Ozonated water effectively reduced the relative abundance of harmful fungi, such as Aspergillus, and Penicillium, and enriched beneficial bacteria, such as Pseudomonas and Actinomycetospora, more effectively than mancozeb and thiophanate-methyl. The results of the study show that ozonated water has potential as a biocide and may be able to replace traditional agents in the future to reduce environmental pollution.